2004
DOI: 10.1002/art.20184
|View full text |Cite
|
Sign up to set email alerts
|

Antiinflammatory and analgesic effects of somatostatin released from capsaicin‐sensitive sensory nerve terminals in a Freund's adjuvant–induced chronic arthritis model in the rat

Abstract: Objective. We previously demonstrated that somatostatin (SOM) released from the activated peripheral terminals of capsaicin-sensitive primary sensory neurons inhibits acute inflammation and nociception. This study was undertaken to examine this systemic "sensocrine" function of neuronally derived somatostatin in chronic inflammation in the Freund's complete adjuvant (CFA)-induced arthritis model.Methods. Arthritis of the tibiotarsal joint of Lewis rats was evoked by subcutaneous injection of CFA into the left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
147
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 163 publications
(154 citation statements)
references
References 44 publications
6
147
1
Order By: Relevance
“…A CGRP antagonist has recently been shown to have a favorable effect in the treatment of pain associated with migraine (50), and it is possible that CGRP is responsible for mediating some of the proinflammatory effects observed after TRPV1 activation. However, sensory nerve-mediated events are more complex in that activated sensory nerves also release antiinflammatory neuropeptides, in particular, somatostatin (51), in and around the joint. It should be noted that if the sum effect of TRPV1 activation is antiinflammatory, one would not expect the deletion of TRPV1 to act in the beneficial manner observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A CGRP antagonist has recently been shown to have a favorable effect in the treatment of pain associated with migraine (50), and it is possible that CGRP is responsible for mediating some of the proinflammatory effects observed after TRPV1 activation. However, sensory nerve-mediated events are more complex in that activated sensory nerves also release antiinflammatory neuropeptides, in particular, somatostatin (51), in and around the joint. It should be noted that if the sum effect of TRPV1 activation is antiinflammatory, one would not expect the deletion of TRPV1 to act in the beneficial manner observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Some groups have demonstrated that TRPV1 plays a potential role in acute and chronic inflammation in the knee joint 4,36) . In contrast, other groups have shown that a TRPV1 agonist 37) and somatostatin 38) attenuate knee joint inflammation. However, there have been no reports using the collagen-induced arthritis model, one of the most important autoimmune models for human rheumatoid arthritis.…”
Section: The Physiological Role Of Trpv1 In Autoimmune Diseasesmentioning
confidence: 73%
“…In this latter situation, more severe systemic signs develop, such as decreased appetite, body weight loss, fever, and diminished mobility (13). The mechanism of joint inflammation in these 2 models involves a T cell-mediated immunologic response, and the histologic picture is very similar to that observed in rheumatoid arthritis (12)(13)(14). Finally, CFA can be given by intraarticular injection, after which it induces a direct, destructive monarthritis localized to the affected joint, with onset within 4-6 hours and increasing intensity over 1-2 weeks (9,14).…”
mentioning
confidence: 92%
“…This approach evokes acute subcutaneous inflammation at the site of injection within a few hours, while arthritis develops ipsilaterally, mainly in the tibiotarsal joint, by the seventh or eighth day after injection. On the contralateral side, much slighter arthritis symptoms develop, from the ninth day through the eleventh day (10)(11)(12). In contrast, CFA can be injected intradermally into the base of the tail to evoke polyarthritis with equal intensity on both sides but mainly in the tibiotarsal joints within 1 week, without soft tissue inflammation of the paws.…”
mentioning
confidence: 99%
See 1 more Smart Citation